Performance assessment of portuguese secondary schools : the society and educational authorities perspectives - M.C. Portela (2009)
This paper describes a performance assessment of Portuguese secondary schools using data envelopment analysis (DEA). The assessment adopts two perspectives: a society perspective where schools are viewed as promoting students achievement given student characteristics in terms of academic abilities and socio-economic background; and an educational authorities perspective where schools are viewed as transforming a set of resources (including student academic abilities, socio-economic background, and also school resources, such as teachers) into students' achievement. Two types of DEA analysis are performed for each perspective: one using an output oriented model allowing factor weights to vary freely from school to school and another using a model that restricts factor weights to be equal for all schools. The first model is well suited for identifying inefficient schools, whereas the latter is best suited for improving discrimination between efficient schools when pursuing the identification of benchmarks. Our sample comprised a small number of schools and therefore the results obtained are mainly illustrative of the potential of the method. Future research will explore the use of this method for the assessment of schools at a national level.